2023
DOI: 10.1037/neu0000884
|View full text |Cite
|
Sign up to set email alerts
|

Further evaluation of narrative description as a measure of cognitive function in Alzheimer’s disease.

Abstract: Objective: The narrative description (ND) test objectively measures the ability to understand and describe visual scenes. As subtle differences in speech occur early in cognitive decline, we analyzed linguistic features for their utility in detecting cognitive impairment and predicting downstream decline. Method: Participants (n = 52) with normal cognition to mild dementia performed the ND test (watched twenty 30-s video clips and described the visual content). Cognitive function was followed for up to 5 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…König et al [58] utilized features of word count, semantic clusters, mean cluster size, and the number of switches. Reeves et al [77] analyzed linguistic features including content efficiency, speech rate, part of speech usage, and unique word counts. The study found that linguistic features varied between subjects with MCI and SCI, and thus can be used for the detection of cognitive impairment.…”
Section: Linguistic Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…König et al [58] utilized features of word count, semantic clusters, mean cluster size, and the number of switches. Reeves et al [77] analyzed linguistic features including content efficiency, speech rate, part of speech usage, and unique word counts. The study found that linguistic features varied between subjects with MCI and SCI, and thus can be used for the detection of cognitive impairment.…”
Section: Linguistic Featuresmentioning
confidence: 99%
“…Several studies used different combinations of features for dementia prediction. Studies showed that the best performance is by a combination of cognitive test scores with other types of features [57,77].…”
Section: Hybrid Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies evaluated whether specific aspects of language competence might be associated with current cognitive status or might predict future cognitive decline. In Reeves et al (2022) study, 52 participants (i.e., healthy subjects, SCD, MCI, and mildly demented patients) watched and subsequently verbally reported the content of short video clips. Simple linguistic features as well as a narrative description score were rated.…”
Section: Languagementioning
confidence: 99%